Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1021/jf048753i
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on Retention of Added Volatiles during Breadcrumb Production

Abstract: Breadcrumb samples were prepared with a range of volatile compounds at known concentrations. The retention of these volatiles was assessed via solvent extraction and quantification by gas chromatography-mass spectrometry. Volatile loss during processing was shown to be substantial and dependent upon the compound's vapor pressure. The influence of initial concentration levels on the retention of volatiles was linear within the bounds of the experimental concentrations (0-300 mg/kg). Comparison of volatile conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In fact, sample A H showed the least retention and D H the most. The maximum difference in fat level between lowand high-fat biscuits was 6% (baked biscuit), and the effects of fat on aroma retention noted in other food systems (Brauss et al 1999;Dimelow et al 2005) were not observed in this biscuit system. The effect of sugar form on anethole retention showed no consistent trend.…”
Section: Mechanical Propertiesmentioning
confidence: 69%
“…In fact, sample A H showed the least retention and D H the most. The maximum difference in fat level between lowand high-fat biscuits was 6% (baked biscuit), and the effects of fat on aroma retention noted in other food systems (Brauss et al 1999;Dimelow et al 2005) were not observed in this biscuit system. The effect of sugar form on anethole retention showed no consistent trend.…”
Section: Mechanical Propertiesmentioning
confidence: 69%
“…Chin et al found that the FD process caused a reduction in the amount of major aroma volatiles in durian pulp, which ranged from 71.5% to 97.2% [ 25 ]. The total loss ratios of the volatile compounds of freeze-dried foods have been reported in some studies, including 50% in coffee extract [ 26 ], 37.5% in banana slices [ 27 ], and 55% in breadcrumbs [ 28 ]. Rajkumar et al found increases and decreases of different extents in concentrations in key volatile compounds of air-dried and freeze-dried cabbages [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 (b), the content of total aroma compounds in red jujube was significantly increased from 11,005 μg/kg to 14,605 μg/kg at stage 0-10. As reported, the average loss ratio of volatile compounds of freeze-dried banana slices and carvone in bread crumbs was 37.5% and 55%, respectively (Dimelow et al, 2005;Mui et al, 2002). It can be seen, pilot scale freeze drying could enhance the aroma compared with traditional constant FD.…”
Section: Dynamic Changes In Aroma Compounds Of Red Jujube During Free...mentioning
confidence: 63%